A questionnaire for a conceptual framework and interdisciplinary public health research using the Delphi technique—development and validation - Alaze, Anita; Finne, Emily; Razum, Oliver; Miani, Céline (Frontiers in Public Health, 2025)
BackgroundThe Delphi technique has become established in public health research, yet there is a lack of methodological standards in questionnaire development. We here demonstrate how the Delphi technique can be used in an interdisciplinary public health topic for framework development, and we highlight methodological challenges and possible solutions.MethodsWe developed the questionnaire through a comprehensive literature review and the generation of an item pool based on the rules of item construction. We used cognitive interviews, a Delphi experts assessment and group discussions to refine the questionnaire and to ensure content validity. Finally, we carried out a pre-test of the online questionnaire.ResultsThe questionnaire consists of three main sections, namely gender (norms), the social environment and the mental health of adolescents, and another section on characteristics of the panelists. It comprises a total of 32 questions and includes rating and ranking questions, content-related and comment questions, open and closed questions as well as questions on personal characteristics and evaluation questions.ConclusionTo address challenges in the development process, interdisciplinary researchers need to be involved. They should consider certain aspects of the development process to provide more structure and clarity, such as comprehensively preprocessing the content, and disentangling and simplifying the theoretical concepts. They should consider a rigorous approach to develop more complex frameworks for interdisciplinary public health topics. Future research should focus on developing methodological guidelines and testing their applicability for different objectives of the Delphi technique (e.g., framework development).